Band-gap-energy-adjustable and noble-metal-free modified NiS-ZnxCd1-xS for highly efficient visible-light-driven Cr6+ photoreduction in alkaline wastewater. (March 2021) - Wang, Linjuan; Zan, Ling
Abstract: Industrial wastewater containing heavy metal ions can cover the full pH range according to the manufacturing process. Alkaline wastewater treatment is still a great challenge because Cr 6+ therein has a more negative reduction potential (Cr2 O7 2−  + 14H +  + 6e −  = 2Cr 3+  + 7H2 O (ECr 6+ (Cr2O7 2− /Cr 3+ )  =  E θ − RT nF ln [ OH ] − ) than in acid solution, in which it can be easily reduced by numerous reagents. In this study, weakly alkaline Cr 6+ solution has been used to simulate weakly alkaline industrial wastewater, and a reagent capable of excellent reduction efficiency therein has been developed. A series of band-gap-energy-adjustable NiS-Zn x Cd1- x S composites has been synthesized by a one-pot hydrothermal method. A more negative conduction band position for Zn x Cd1- x S has been achieved by doping and changing the amount of Zn 2+ ions to ensure a superior photoreduction ability. All modified samples show excellent photocatalytic efficiency. For example, the reduction efficiency of 10%NiS–Zn0.25 Cd0.75 S sample is threefold higher than that of Zn0.25 Cd0.75 S and sixfold higher than that of CdS when deployed at a catalytic level for 30 min. Multiple characterization methods have been applied, and the results show that the improved efficiency can be ascribed to intimate contact between Zn0.25 Cd0.75 S and NiS. Photoluminescence (PL) and photocurrent measurements and electrochemical impedance spectroscopy (EIS) further elucidate the catalytic mechanism and imply an enhanced charge-carrier separation efficiency between Zn0.25 Cd0.75 S and NiS. Graphical abstract: Image 1 Highlights: A series of Zn x Cd1- x S composites were synthesized through a facile one-pot method. NiS-Zn0.25 Cd0.75 S composites show a high efficiency of photocatalytic. Intimate contacts were observed between Zn0.25 Cd0.75 S and NiS by XPS. PL, photocurrent, and EIS measurements elucidated the photocatalytic mechanism.